Digitalisasi Pengelolaan Zakat, Efisiensi dan Kepatuhan Muzaki di Indonesia - A. Fahrur Rozi; Ana Nurwakhidah; Irfan Faroqi (Universitas Islam Raden Rahmat, 2026)
This study addresses the discrepancy between the rapid digitalization of zakat management and the suboptimal efficiency of zakat institutions and muzakki compliance in Indonesia. The research aims to describe the development of zakat digitalization, analyse its influence on institutional operational efficiency and muzakki compliance, and identify supporting and inhibiting factors in its implementation. This study employs a library research method by examining relevant literature, books, journals, reports, and scientific studies as primary and secondary data sources. The findings indicate that digitalization offers opportunities to enhance service quality, yet its effectiveness depends heavily on institutional readiness, governance quality, and muzakki trust. The study concludes that technology alone is insufficient without system integration and strengthened institutional capacity.